ANALISIS PERKEMBANGAN EKONOMI ISLAM DI INDONESIA - Ahmad Fauzan Purba; Dava Maulana Tanjung (CV. ADIBA AISHA AMIRA, 2023)
Islamic economic is an economic system that has a legal basis. Islamic law. This is true even though Islamic economic refersto the basic of Islamic law. It does not prevent non-muslim from participating in the Islamic economic system. Basically, Islamic economic amis to achieve prosprerity ; There are many countries where are majority does not achieve a majority because profit is not the only goal. The community is muslim or the economy is liberal. Islam is seen from various aspects. Islam economic is applied in various countries. Primadonna is a sharia bank which an Indonesia is called a sharia bank. Thus, in the Islamic prespective, prospereti is not only about material goods but olso considers happiness in life after death